Microestrutura e propriedades mecânicas de vitrocerâmicos do sistema Li2O – CaO – SiO2 - Santos, Gisele Guimarães dos (2013)
An interesting characteristic of the Li2O-CaO-SiO2 glass-forming system is the possibility of obtaining certain crystalline phases and morphologies that may lead to tough glass-ceramics. However, very few published works investigated this matter. Glass compositions within the range 30-50% CaSiO3 / 70-50% Li2SiO3 were studied to obtain appropriate microstructures. Heat treatments were conducted using the double treatment technique: nucleation at about the glass transition temperature followed by crystal growth within the temperature range 500 and 700°C. These temperatures were selected according to DSC data. The influence of the size, number and morphology of the crystals on certain mechanical properties of the glass-ceramics, such as hardness and indentation toughness, were estimated by Vickers indentation tests. The samples were also characterized by X-ray diffraction to identify the phases present and by MEV to examine the crystal size, percentage and morphology. The best results were obtained with a composition of 44% mol CaSiO3 using the following thermal treatment conditions: 498°C for 24 hours (nucleation) and 700°C for 2 hours (Crystal growth), that led to a glass-ceramic showing a toughness of 1,9 MPa.m1/2.